Awareness of personal financial planning among the employees; case study: Putra Specialist Hospital (Melaka) Sdn Bhd / Nur Faizah Tahwan - Tahwan, Nur Faizah (2011)
Previous research conducted found that an overuse of credit, overspending, lack of budgeting, too many debts, inadequate shopping and spending skills, low salary and lack of knowledge about money are the main factors that contribute to financial problems. Proper personal financial planning will allow an individual to live a comfortable life in his or her golden years without the need for concern on any financial constraint. This study is to determine relationship financial literacy, the attitudes towards personal financial planning and frequency of managing personal financial planning with awareness of personal financial literacy. A survey data was obtained from 50 of respondents by using a set of structured questionnaire. The data obtained from questionnaires and secondary data were analyzed using SPSS version 14.0. From the result, financial literacy has a good and positive relationship with awareness of personal financial planning compared with attitudes toward personal financial planning and frequency of managing it. The recommendation and limitation were also included to assist those future researches who are interested to study further on this topic.